Ploidy Levels and Fitness-Related Traits in Purebreds and Hybrids Originating from Sterlet (Acipenser ruthenus) and Unusual Ploidy Levels of Siberian Sturgeon (A. baerii) - Shivaramu, Sahana; Lebeda, Ievgen; Vuong, Doi Thi; Rodina, Marek; Gela, David; Flajšhans, Martin (Genes, 2020)
The present study aimed to investigate and compare fitness-related traits and ploidy levels of purebreds and hybrids produced from sturgeon broodstock with both normal and abnormal ploidy levels. We used diploid Acipenser ruthenus and tetraploid A. baerii males and females to produce purebreds and reciprocal hybrids of normal ploidy levels. Likewise, we used diploid A. ruthenus and tetraploid A. baerii females mated to pentaploid and hexaploid A. baerii males to produce hybrids of abnormal ploidy levels. Fertilization of ova of A. ruthenus and A. baerii of normal ploidy with the sperm of pentaploid and hexaploid A. baerii produced fully viable progeny with ploidy levels that were intermediate between those of the parents as was also found in crosses of purebreds and reciprocal hybrids of normal ploidy levels. The A. ruthenus × pentaploid A. baerii and A. ruthenus × hexaploid A. baerii hybrids did not survive after 22 days post-hatch (dph). Mean body weight and cumulative survival were periodically checked at seven-time intervals. The recorded values of mean body weight were significantly higher in A. baerii × pentaploid A. baerii hybrids than other groups at three sampling points (160, 252 and 330 dph). In contrast, the highest cumulative survival was observed in A. baerii × A. ruthenus hybrids at all sampling points (14.47 ± 5.70 at 497 dph). Overall, most of the studied sturgeon hybrids displayed higher mean BW and cumulative survival compared to the purebreds. The utilization of sturgeon hybrids should be restricted to aquaculture purposes because they can pose a significant genetic threat to native populations through ecological interactions.
Keywords: Animals; Ploidies; Female; Chimera; spermie; ženské pohlaví; Spermatozoa; Oocytes; fitness-related traits; polyploidy; Fishes; genom; oocyty; ploidie; Genome; Evolution, Molecular; molekulární evoluce; ryby; restocking; Chromosomes; Male; sturgeons; aquaculture; chiméra; zvířata; mužské pohlaví; chromozomy